Profile of Cancer Patients Referred for Radiotherapy in West Kalimantan: A Hospital-Based Descriptive Study at RSUD Dr. Soedarso Pontianak in 2024 - Uray Ria Aprini; Rendhy Tito Apreza (Jurnal Impresi Indonesia, 2026)
Cancer remains a major global health burden, with increasing incidence and mortality rates, particularly in developing countries such as Indonesia. Despite its essential role in cancer management, data regarding radiotherapy utilization in West Kalimantan are still limited. This study aims to describe the demographic and clinical profile of cancer patients referred for radiotherapy at RSUD Dr. Soedarso Pontianak in 2024. A quantitative descriptive study with a retrospective design was conducted using total sampling of 369 patients. Data were collected from medical records and analyzed descriptively using frequency distributions and percentages. The variables analyzed included sex, age group, region of origin, and cancer diagnosis. The results showed that the majority of patients were female (70%), with the most common age group being 41–49 years (32.8%). Most patients originated from Pontianak (28%), followed by Kubu Raya and Sintang. The most common cancer diagnosis was breast cancer (27%), followed by cervical cancer (26%) and nasopharyngeal cancer (18%). These findings highlight the predominance of female-related cancers and the influence of geographic accessibility on radiotherapy utilization. In conclusion, the profile of cancer patients referred for radiotherapy in this hospital is dominated by middle-aged women with breast cancer, emphasizing the need for improved cancer screening, early detection programs, and equitable access to radiotherapy services in West Kalimantan.